Knowledge towards Prevention and Early Detection of Chronic Kidney Disease and Associated Factors among Hypertensive Patients at a Chronic Illness Clinic of Jimma Town Public Hospitals. (22nd October 2020) - Tegegne, Belachew; Demeke, Tigist; Amme, Shemsedin; Edmealem, Afework; Ademe, Sewunet
Abstract : Background . Morbidity and mortality due to chronic kidney disease are increasing among hypertensive patients in Sub-Saharan Africa. The majority of hypertensive patients with chronic kidney disease are not diagnosed at an early stage because of poor knowledge. However, to the best of our knowledge, there is no study conducted in Ethiopia about knowledge of hypertensive patients towards prevention and early detection of chronic kidney disease. Thus, the aim of this study was to assess knowledge towards prevention and early detection of chronic kidney disease and associated factors among hypertensive patients at Jimma town public hospitals, Ethiopia. Methods . A hospital-based cross-sectional study was conducted among 332 hypertensive patients using an interviewer-administered questionnaire and medical record reviewing from April 5 to May 21, 2019. Study participants were selected using simple random sampling. Data were collected by using a standardized questionnaire. Data were entered into Epidata version 3.1 and analyzed by SPSS version 23. Descriptive statistics and bivariable and multivariable logistic regression were applied. To identify factors, a 95% confidence level and P value of less than 0.05 were considered. Results . Over half (59.6%) were males, and the mean (±SD) age of participants was 54.92 (12.91) years. Among the total participants, more than half of them (47.9%) had good knowledge. Attending secondary education (AOR = 2.9, P = 0.014 ), higher education (AOR = 5.4, P = 0.001 ), working in private sectors (AOR = 4.3, P = 0.001 ), taking three and above drugs per day (AOR = 0.55, P = 0.016 ), and having a family history of kidney disease (AOR = 2.3, P = 0.012 ) were significantly associated with knowledge. Conclusion and Recommendation . Near to half of the study participants had good knowledge towards prevention and early detection of chronic kidney disease. Attending secondary education and above, working in private sectors, taking three and above drugs per day, and having a family history of kidney disease were independent predictors of knowledge. Hypertensive patients should be encouraged to be aware of risk factors of CKD, and health care providers should educate hypertensive patients about the prevention and early detection of chronic kidney disease.